The Impact of Translating English Haiku on the Emergence of Haiku in Persian Literature - Fatemeh Parham; Meead Jahantigh (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This study aims to conduct a comparative analysis of translated English haikus and Iranian haikus, exploring whether Persian haikus (composed in Persian) exhibit literary characteristics influenced by translated haikus or possess distinct traits. To this end, an integrated model of haiku evaluation was developed. Subsequently, 150 English haikus and their corresponding Persian translations were evaluated according to this model, elucidating the features of the translated haikus. The evaluation entailed not only formal aspects such as syllable count and line structure but also semantic nuances. Furthermore, 100 Iranian haikus were assessed using the same integrated model, enabling a comparison between translated and Iranian haikus to identify their commonalities and differences. The findings reveal two discernible categories of Iranian haikus: one influenced by translated haikus, characterized by classical elements rooted in Japanese culture, and another type of haiku with an inherent Iranian identity, inspired by Iranian culture and distinct in its expression.